The effect of opening on building envelope toward daylight performance in Betang House at Central Borneo - Eka Susanti; Desak Putu Damayanti; Sri Nastiti N. Ekasiwi; Ima Defiana (IPTEK Journal of Proceedings Series, 2017)
The traditional house is able to adapt the climate around them and it can reduce the burden of energy use to adjust the comfort of occupants. The development pattern of occupants’ activity adjusts to a modern life that indirectly affects the function and condition of the building. This gives rise to a new phenomenon, whether development sheath openings in buildings can still meet the needs of lighting for the activity of the occupants. This research was conducted with the aim to clarify and identify the deployment sheath openings in buildings on the performance of natural lighting in Betang House. The method experiment with the help simulation is used to find a causal relationship from deployment sheath openings in Betang House building performance against natural lighting. The experiment is conducted with the simulation using Autodesk Ecotect Analysis 2011. The final result of the research indicates deployment openings in the façade have natural lighting performance that already meet the standards of the lighting for the activity. Deployment openings with the addition of extents openings could increase illuminantion and daylight factor space by 10% and 14%, but the value of the resulting illuminantion uniformity is not too high. The addition of height can increase the value of daylight factor of 13%. The ratio of lighting uniformity additional height opening is higher, but that resulted being lower illuminantion 0.3%. Rumbak tahansengan deployment at facade can improve the ratio of the lighting uniformity for activity up to 9.6%.